Access to work for disabled persons in South Africa : the intersections of social understandings of disability, substantive equality and access to social security - Du Plessis, Meryl Candice (Department of Commercial Law, 2015)
This thesis examines possible synergies and points of friction between understandings of disability that emphasise its social contingency and jurisprudential debates on substantive equality and access to social security in the context of the promotion of access to work for disabled persons in South Africa. In consequence of an analysis of theoretical debates in the field of disability studies and how these find application in the sphere of employment equity law, it is concluded that, while social understandings of disability mostly focus on structural changes that would see people with disabilities who can and want to work gain access to such work, the positive obligations imposed on employers and the state in terms of equality rights and employment equity legislation are of limited depth and breadth. It is proposed that one potential course of action to address the limited scope of equality law would be to emphasise the state's obligations in terms of socio-economic rights where these rights are relevant to work inequality. Particular emphasis is placed on how the interpretation and application of the right to access to social security could be used to activate government's duties in respect of unemployment protection and work creation. The conclusion reached is that while this strategy poses risks and has its limitations, it can be used to improve information gathering in respect of disabled work seekers that will aid planning and enforcement; to facilitate support for disabled work seekers who experience discrimination; to compel government to improve the implementation and enforcement of employment equity laws in respect of disabled work applicants; to catalyse a holistic approach to social security that considers the interrelationship between social assistance and promoting unemployment protection for disabled persons who are willing and able to work; and to provide different forms of support to disabled people who do not operate in the formal labour market, but who can and do perform work that falls outside the scope of traditional labour market regulation.